Honey, its Quality and Composition and their Responsible Factors - Sharma, Rohini; Thakur, Meena; Rana, Kiran; Devi, Diksha; Bajiya, Mangla Ram (International Journal of Bio-resource and Stress Management, 2023)
Honey is a sweet viscous food substance made by honey bees. It contains more than 180 nutritional substances, due to which it is known for boosting immunity. Honey is comprised of easily digestible honey sugars and energy providing nutrients. It is used as an ingredient in hundreds of manufactured foods for its sweetness, colour, flavor, caramelization and viscosity. It’s various physicochemical constituents, moisture content (<25%), reducing sugars (>65%), acidity (<0.2%), electrical conductivity (<0.8 mS/cm for blossom honey), sucrose content (5%), hydroxy methyl furfuraldehyde (HMF) (<40 mg kg-1) etc. contribute to its nutritional quality, granulation, flavor, texture, fermentation and storage quality. Other properties viz. diastase content, proline content, phenols, pollen density etc. are important indicator of quality and origin of honey. Honey is the reservoir of different minerals, with potassium being most abundant element. Owing to its chemical composition, honey has been reported to have significant impact on human nutrition and health. Its quality is evaluated based on standard quality parameters standardized by different authorities. The quality and composition of honey highly depends on the type of flowers utilized by the bees, climatic conditions and various other factors like floral sources, seasons, beekeeper activities, harvesting of honey, processing, storage, agrochemicals, adulteration and geographical origin. The demand of honey is also increasing in upward trend; thus, the analysis of these quality parameters helps us to ensure that the honey we are consuming fulfills the required parameters.